(untitled) (PETITUM, 2026)
The results of the study show that the application of Article 111 paragraph (2) of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics in decision number 122/pid.Sus/2022/PN.Tka is inappropriate because the judge should have considered the element of criminal conspiracy because in the case in question there was more than one perpetrator (delnemiing) as regulated in Article 1 number (18) of Law Number 35 of 2009 concerning Narcotics. And the formulation of the indictment made by the public prosecutor is an unclear indictment (obscure liebels). Because the legal facts and the imposition of the article do not match. The appropriate article to apply in this case is Article 114 Paragraph (2) of Law Number 25 of 2009 concerning narcotics Jo. Article 132 paragraph (1) of the Narcotics Law, because based on the data and facts obtained by the author, the case constitutes a criminal conspiracy to commit the crime of buying and acting as an intermediary for the sale and purchase of class I narcotics of the plant type marijuana.